Short-Term Follow-Up Treatment of Thumb Carpometacarpal Joint Osteoarthritis Through Total Arthroscopic Trapeziectomy with Suture-Button Suspensionplasty - Martin Lozoya, Jorge; Corella, Fernando; Ocampos Hernandez, Montserrat; Carnicer, Maria Isabel; Laredo, Rafael; Larrainzar-Garijo, Ricardo (Journal of Wrist Surgery, 2025)
The surgical management of thumb carpometacarpal osteoarthritis is extensive, with numerous techniques describing both open and arthroscopic approaches. However, there is limited literature on the outcomes of arthroscopic trapeziectomy.The primary objective of this study is to evaluate the clinical and functional outcomes of total arthroscopic trapeziectomy combined with suture-button suspensionplasty. The secondary objective is to assess patient satisfaction with the surgery.We evaluated a total of 42 patients (34 women) with a mean age of 62.34 years, all diagnosed with severe trapeziometacarpal osteoarthritis according to Eaton's classification (grades III and IV). Measurements were taken preoperatively and more than 1 year postoperatively, including range of motion, Kapandji test, pinch strength (tip-to-tip and key pinch), and grip strength (Jamar). All patients completed the disabilities of the arm, shoulder, and hand (DASH) questionnaire and visual analog scale (VAS) for pain. Finally, patient satisfaction levels were recorded at 1 year postsurgery.The mean preoperative DASH and VAS scores were 48.81 ± 17.97 and 7.2 ± 1.48, respectively, showing significant improvement to 7 ± 10.32 and 0.52 ± 1.50 at 1 year postoperatively (p < 0.05). We found a significant weak positive correlation between the collapse of the first metacarpal and the DASH and VAS scores (p < 0.05). Regarding the range of motion, similar results were found in terms of range (palmar and radial abduction and Kapandji test) compared with preoperative values. Pinch strength showed slight improvements in tip-to-tip strength (3.2 ± 1.69 vs. 3.42 ± 1.75) and JAMAR grip strength (15.76 ± 9.53 vs. 17.61 ± 9.64), with a slight decrease in key pinch strength (4.26 ± 2.29 vs. 4.11 ± 1.68), although these differences were not statistically significant. The mean patient satisfaction was 4.5/5, with less than 5% of the sample rating their satisfaction below 3/5 postsurgery.Total arthroscopic trapeziectomy combined with suture-button suspensionplasty is an effective technique for improving pain and hand disability in patients with severe trapeziometacarpal osteoarthritis.2b therapeutic, individual cohort study.
Keywords: thumb carpometacarpal osteoarthritis; total trapeziectomy; arthroscopy